2021
DOI: 10.1126/sciadv.abf6222
|View full text |Cite
|
Sign up to set email alerts
|

Survival of presolar p -nuclide carriers in the nebula revealed by stepwise leaching of Allende refractory inclusions

Abstract: The 87Rb-87Sr radiochronometer provides key insights into the timing of volatile element depletion in planetary bodies, yet the unknown nucleosynthetic origin of Sr anomalies in Ca-Al–rich inclusions (CAIs, the oldest dated solar system solids) challenges the reliability of resulting chronological interpretations. To identify the nature of these Sr anomalies, we performed step-leaching experiments on nine unmelted CAIs from Allende. In six CAIs, the chemically resistant residues (0.06 to 9.7% total CAI Sr) sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 62 publications
1
22
0
Order By: Relevance
“…Depending on the version, the amplifiers show different responses to any instrumental trouble in the constant current generator. This idea does not contradict with previous studies 17–19 that reported no systematic error in the isotopic data obtained by TIMS using the 3.3 pA constant current calibration.…”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…Depending on the version, the amplifiers show different responses to any instrumental trouble in the constant current generator. This idea does not contradict with previous studies 17–19 that reported no systematic error in the isotopic data obtained by TIMS using the 3.3 pA constant current calibration.…”
Section: Resultssupporting
confidence: 77%
“…A new calibration technique for the 10 13 U Faraday amplier was recently reported to achieve better precision in gain measurement. [16][17][18][19] This technique employs a fully sowarecontrolled procedure that entails the use of a 3.3 pA constant current generator, while the automation of the calibration protocol tends to obscure technical or instrumental problems. In practice, our preliminary isotopic data yielded a systematic error of >0.1&, suggesting a need for the validation of the calibration protocol prior to an isotopic analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, this study shows that while the precision of LA-MC-ICP-MS/MS is not as good as TIMS, which has a better useful yield than LA-MC-ICP-MS/MS for Sr (1.5% (ref. 97) vs. 0.25%), the precision is still sufficient to detect magma mixing and assimilation based on in situ 87 Sr/ 86 Sr isotopic analyses.…”
Section: Magma Sources In the 265 Ka Oruanui Supereruptionmentioning
confidence: 98%
“…Our motivation for measuring the Sr isotopic compositions of hibonite inclusions was to search for possible isotopic anomalies 108 and compare the 87 Sr/ 86 Sr ratios with the known solar system initial ratio (0.69876 AE 0.00002; 109 0.69883 AE 0.00002; 110 0.698784 AE 0.000076 (ref. 97)). Given the small size and refractory nature of hibonite inclusions, we changed the laser beam spot to 35 mm and the repetition rate to 12 Hz.…”
Section: Meteoritic Hibonite Inclusionsmentioning
confidence: 99%
“…To quantitatively assess the expected μ 84 Sr variations, we will start with the variations expected from the heterogeneous distribution of nuclides produced in neutron-rich stellar environments. For Sr this includes r-and p-process variations, which result in the same 84 Sr signatures; for instance, the 84 Sr excesses in CAIs have been interpreted to reflect either an r-process (Hans et al 2013) or p-process excess (Charlier et al 2021). For the model of this study, the distinction between r-and p-process variations is not important, which we will therefore treat together.…”
Section: Sr Homogeneity Of the Inner Solar Systemmentioning
confidence: 99%